3D printed Ti-5Cu alloy accelerates osteogenic differentiation of MC3T3-E1 cells by stimulating the M2 phenotype polarization of macrophages - Zhao, Xin; Zhou, Xing; Sun, Hui; Shi, Huixin; Song, Yiping; Wang, Qiang; Zhang, Guangping; Xu, Dake (Frontiers in Immunology, 2022)
Ti-5Cu alloy has been proved to have excellent mechanical properties and cell compatibility and has certain antibacterial properties due to the addition of Cu. However, there are few studies on the effects of Ti-5Cu alloy on macrophage polarization and immune-related bone formation. In this study, we prepared Ti-5Cu alloy by three-dimensional printing technology and found that Ti-5Cu alloy presented a much smoother surface compared with Ti. In addition, the CCK-8 results indicated the Ti-5Cu alloy had no cytotoxicity to RAW264.7 cells by co-culture. The results of inductively coupled plasma mass spectrometry showed that the concentration of Cu2+ was 0.133 mg/L after 7 days of co-culture, and the CCK-8 results proved that Cu2+ had no cytotoxicity to RAW264.7 at this concentration. Then, we studied the effects of Ti-5Cu alloy on macrophage polarization; it was shown that the Ti-5Cu alloy is more prone to modulate the RAW264.7 polarization towards the M2 phenotype and the conditioned medium derived from Ti-5Cu alloy significantly promoted the proliferation and osteogenic differentiation of MC3T3-E1 cells. However, when the expression of Oncostatin M (OSM) gene of RAW264.7 was knocked down, the osteogenic differentiation of MC3T3-E1 cells was decreased. This suggests that the OSM secreted by RAW264.7 co-cultured with Ti-5Cu alloy could accelerate the osteogenic differentiation of MC3T3-E1 cells by acting on OSMR/gp130 receptors.